Revitalizing Creativity: Enhancing Students' Creative Thinking through STEAM and Project-Based Learning in Human Respiration Studies - Panduweni, Maidina; Suhartini, Erna; Haerani, Rosita Putri Rahmi (Scientiae Educatia: Jurnal Pendidikan Sains, 2024)
One of the skills that students need to face global competition is the ability to think creatively. This study aims to determine the effect of applying the STEAM approach with the Project-Based Learning (PjBL) model on improving students' creative thinking skills on human respiratory system material in primary schools. The type of quantitative research used is experimental research. The type of experimental research employed is quasi-experimental with a non-equivalent control group design. The data analysis techniques used in this study were normality test, homogeneity test, and hypothesis testing using independent samples t-test. The research results from hypothesis testing using the Independent Samples t-test show that the Sig. (2-tailed) value is 0.000, indicating that H0 is rejected and H1 is accepted. Thus, because the value of Sig. (2-tailed) obtained is less than 0.05, it can be concluded that there is an effect of STEAM using the Project-Based Learning model on the creative thinking skills of students in Class V Human Respiratory System Science Material at SDN 011 Kota Samarinda. The increase in the creative thinking skills of the students in the experimental group was 0.42 and was placed in the medium category. In conclusion, the application of the STEAM approach combined with the Project-Based Learning model significantly enhances the creative thinking skills of primary school students in the context of human respiratory system material.